Fides and bona fides in the process of creating ius gentium (Fides и bona fides у процесу стварања римског општег права (ius gentium) - Sič, Magdolna (Zbornik radova Pravnog fakulteta u Novom Sadu, 2012)
Regarding the puzzling question of Roman law, why fides as a principle of behavior was changed during the pre-classical period into bona fides and whether the adjective bona changes the meaning of fides, the author comes to the following conclusions: The sources point to the fact that the fides was in archaic and pre-classical period used as a basic principle of bahavior in public and as well in privat law relations of Romans with other nations. The Romans acted according to this principle also in their internal public law relations. Fides had a wide meaning: it meant behaving as a honorable and correct men, faith (honesty), trust and trustworthyness, as well as an obligation to protect the other party. In that sense fides was a universal principle. As far as the Romans themselves are concerned, fides had also a wider meaning and signified a behavior according to the rules of mos maiorum. The adjective bona appears to regulate newly emerged private law relations in the Roman society. The author joins the opinion of Carcaterra, that this adjective (which in documents sometimes stands alone), served for clarification of wide, and therefore also the undetermined notion of fides, in concrete private law relations. Bona was most probably at the beginning perceived as good behavior in accordance with the rules of mos maiorum. This way, by adding bona to fides started the creation of a new business ethics. Only after some time, in the light of solving more complex problems of business dealings by pre-classical and especially classical jurisprudence, bona fides turned into a standard of honest behavior in business relations. Taking into consideration that the concept of fides and bona fides relates not just business relations of Romans themselves, but also their business dealings with other nations, the following question emerges: was bona fides firstly introduced into the edict by the peregrine praetor, or this principle has been already applied earlier within ius civile? This question however, i.e. the emergence of bonae fidei iudicia, due to its complexity, will be discussed in a separate paper. Поводом сложене проблематике промене fides у bona fides у току преткласичног римског права, после кратког увода (1) разматрају се следећа питања: појам и улога fides у римској заједници (2); да ли је fides обавезивала само римске грађане или и припаднике других народа (3); разлози преображаја fides у bona fides у приватно правним односима (4), да би се стигло до закључка о потреби разјашњења неодређеног појма fides у свакодневним односима размене путем придева bona у смислу доброг (поштеног) понашања (5). Остаје отворено питање: да ли је до ове промене дошло делатношћу перегринског претора или у оквиру цивилног права?